Predictive Factors That May Contribute to Secondary Insults With Nursing Interventions in Adults With Traumatic Brain Injury. Issue 1 (February 2017) - Nyholm, Lena; Howells, Tim; Enblad, Per
Abstract : ABSTRACT: Background: Nursing interventions pose risks and benefits to patients with traumatic brain injury at a neurointensive care unit.Objectives: The aim of this study was to investigate the risk of inducing high intracranial pressure (ICP) related to interventions and whether intracranial compliance, baseline ICP, or autoregulation could be used as predictors.Methods: The study had a quantitative, prospective, observational design. Twenty-eight patients with TBI were included, and 67 interventions were observed. The definition of a secondary ICP insult was ICP of 20 mm Hg or greater for 5 minutes or more within a continuous 10-minute period.Results: Secondary ICP insults related to nursing interventions occurred in 6 patients (21%) and 8 occasions (12%). Patients with baseline ICP of 15 mm Hg or greater had 4.7 times higher risk of developing an insult. The predictor with the best combination of sensitivity and specificity was baseline ICP.Conclusions: Baseline ICP of 15 mm Hg or greater was the most important factor to determine the risk of secondary ICP insult related to nursing intervention.